Effect of Aquatic Vegetation on the Persistence of Cypermethrin Toxicity in Water - Mugni, Hernán Diego (2011)
Soybean production in Argentina comprises 15 million ha. Cypermethrin is the main insecticide applied amounting 150 g of active ingredient per hectare, thus representing roughly 2.3 thousand tons yearly released to the environment. Toxicity pulses have been observed in small streams draining agricultural basins, most of them sustaining macrophyte growth. Cypermethrin concentrations and its toxicity to the amphipod Hyalella curvispina was compared following an addition to laboratory mesocosms with and without a vegetation cover of the floating macrophyte Lemna sp. Both concentrations and toxicity decreased faster in the treatments covered with Lemna. Fast adsorption of the hydrophobic pesticide to the roots and fronds of Lemna was suggested.